Association between work schedules and motivation for lifestyle change in workers with overweight or obesity: a cross-sectional study in Japan - Miho Kimachi; Shunichi Fukuhara; Yosuke Yamamoto; Yukihiro Tanikawa; Minoru Ishikawa; Tomoichiro Hisada (BMJ Open)
Objective To investigate the association between work schedules and motivation for behavioural change of lifestyle, based on the transtheoretical model (TTM) in workers with overweight or obesity.Design A cross-sectional observational study.Setting A healthcare examination centre in Japan.Participants Between April 2014 and March 2016, we recruited 9243 participants who underwent healthcare examination and met the inclusion criteria, namely, age 20–65 years, body mass index (BMI) ≥25 kg/m2 and full-time workers.Exposure Night and shift (night/shift) workers were compared with daytime workers in terms of motivation for behavioural change.Primary and secondary outcome measures The primary outcome was action and maintenance stages of change (SOC) for lifestyle in TTM. In a subgroup analysis, we investigated interactions between characteristics, including age, sex, BMI, current smoking, alcohol habits, hours of sleep and working hours.Results Overall, 1390 participants (15.0%) were night/shift workers; night/shift workers were younger (median age (IQR): 46 (40–54) vs 43 (37–52) years) and the proportion of men was lesser (75.4 vs 60.9%) compared with daytime workers. The numbers of daytime and night/shift workers in the action and maintenance SOC were 2113 (26.9%) and 309 (22.2%), respectively. Compared with daytime workers, night/shift workers were less likely to demonstrate action and maintenance SOC (adjusted OR (AOR): 0.85, 95% CI: 0.74 to 0.98). In a subgroup analysis that included only those with long working hours (≥10 hours/day), results revealed a strong inverse association between night/shift work and action and maintenance SOC (AOR: 0.65, 95% CI: 0.48 to 0.86). A significant interaction was observed between long working hours and night/shift work (P for interaction=0.04).Conclusions In workers with overweight or obesity, a night/shift work schedule was associated with a lower motivation for behavioural change in lifestyle, and the association was strengthened in those with long working hours.